Impact of Type 2 Diabetes Mellitus on Bone Healing in Patients with Long Bone Fractures: A Cross- Sectional Clinical Study - Muhammad Faheem Kausar, Sibtain Raza, Salman Ahmad Siddiqui, Aisha Asim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder that adversely affects bone metabolism and fracture repair. Impaired angiogenesis, accumulation of advanced glycation end products, and compromised immune function contribute to delayed healing and higher complication rates in diabetic patients. Objective: To evaluate the impact of T2DM on bone healing in patients with long bone fractures and to compare healing outcomes with non-diabetic patients. Methods: This cross-sectional clinical study was conducted at the Department of Orthopedic Surgery, University of Lahore Teaching Hospital, Lahore, Pakistan, between June 2022 and February 2023. A total of 90 patients with acute long bone fractures were included, comprising 45 diabetic and 45 non-diabetic patients. Demographic data, fracture characteristics, glycemic control (HbA1c), and treatment modalities were recorded. Healing outcomes were assessed clinically and radiologically at 6, 12, and 16 weeks. Delayed union, nonunion, and postoperative infection rates were documented. Data were analyzed using SPSS version 26, with independent t-tests and chi-square tests applied. A p-value < 0.05 was considered significant. Results: The mean healing time was significantly prolonged in diabetics (16.4 ± 2.6 weeks) compared to non-diabetics (12.7 ± 2.1 weeks, p < 0.001). Delayed union occurred in 33.3% of diabetics versus 8.9% of non-diabetics (p = 0.004). Nonunion was observed in 11.1% of diabetics compared to 2.2% of controls. Postoperative infections were also higher in diabetics (17.8%) than non-diabetics (4.4%, p = 0.046). Conclusion: T2DM significantly delays bone healing and increases the risk of delayed union, nonunion, and postoperative infections in patients with long bone fractures. Strict glycemic control and comprehensive perioperative management are essential to optimize healing outcomes in diabetic patients. Keywords: Type 2 Diabetes Mellitus, Bone Healing, Long Bone Fractures, Delayed Union, Nonunion